Misleading acts in the Directive of unfair commercial practices - Salgado André, Elena (Revista Jurídica Portucalense, 2018)
The present paper analyzes the art. 6 of the Directive of unfair commercial practices, with the purpose of identifying the requirements that determine its qualification as unfair. For this, after some introductory considerations, which refer to the complex structure of the unfair commercial practices prohibition in the Community legislation, an examination is made about the legal precept dealing with misleading acts.